Preliminary Analysis of the Nonsynonymous Polymorphism rs17563 in BMP4 Gene in Brazilian Population Suggests Protection for Nonsyndromic Cleft Lip and Palate. (27th November 2012) - Araújo, Tânia Kawasaki; Simioni, Milena; Félix, Têmis Maria; de Souza, Liliane Todeschini; Fontes, Marshall Ítalo Barros; Monlleó, Isabella Lopes; Souza, Josiane; Fett-Conte, Agnes Cristina; Secolin, Rodrigo; Lopes-Cendes, Iscia; Maurer-Morelli, Cláudia Vianna; Gil-da-Silva-Lopes, Vera Lúcia
Abstract : Cleft lip with or without palate (CL±P) is common congenital anomalies in humans. Experimental evidence has demonstrated that bone morphogenetic protein 4 gene ( Bmp4 ) is involved in the etiology of CL±P in animal models. The nonsynonymous polymorphism rs17563 T>C (p.V152A) in the BMP4 gene has been associated to the risk of nonsyndromic CL±P in Chinese population and microforms from different ethnic backgrounds. The aim of this study was to investigate the role of BMP4 gene in CL±P in Brazilian sample using genetic association approach. Our sample was composed by 123 patients with nonsyndromic CL±P and 246 controls, in which absence of CL±P was confirmed in 3 generations. The rs17563 polymorphism was genotyped by PCR-RFLP technique. Logistic regression was performed to evaluate allele and genotype association. Our data showed statistical power to detect association (86.83%) in this sample. Logistic regression results showed significant association between C allele and CL±P (P = 0.00018, OR= 0.40, and 95% CI = 0.25–0.65), as well as CC genotype and CL±P (P = 0.00018, OR= 0.35, and 95% CI = 0.19–0.66). So, there is a strong association between nonsyndromic CL±P and BMP4 rs17563 polymorphism in our sample and the C allele had a protective effect against the occurrence of nonsyndromic CL±P.